Why K-12 education is important to achieving a Weather-Ready Nation. Issue 2 (3rd April 2023) - Lanicci, John M.; McCorrison, Sarah K.
Abstract: We propose the formal inclusion of the K-12 education system as a critical step to achieving the National Weather Service's (NWS) vision of a Weather Ready Nation (WRN). The WRN is a NWS initiative to build resilience within the U.S. population to extreme weather, water, and climate events, and includes considerable research investments in science and technology and social, behavioral, and economic science (SBES). The SBES research has been focused on weather communications/messaging and development of impacts-based products, with the goal of better-informed decisions by the public during hazardous weather. While there is a long history of educators working with meteorological professionals on educational initiatives within the K-12 system, the majority of these efforts have involved individual educator initiatives. We believe that including K-12 educators as formal stakeholders in the NWS WRN strategy is one of the most effective ways to reach the greatest segment of the population, and our limited literature review reveals evidence of educational efforts leading to better preparedness. We suggest that formally integrating K-12 educators as partners can best be accomplished by creating a committee of NWS meteorologists, emergency managers, school administrators, and faculty in order to ensure that each partner's concerns are addressed. The curriculum itself should be designed to "connect the dots" from meteorological theory to hazardous weather, hazard products and understanding them to make safe, informed decisions during dangerous weather. We recommend testing this curriculum through a pilot study in a single district or school, with a longitudinal component to monitor its effectiveness.